COVID-19 and cognitive performance: a Mendelian randomization study - Tang, Ching-Man; Li, Gloria Hoi-Yee; Cheung, Ching-Lung (Frontiers in Public Health, 2023)
Background: A substantial proportion of individuals with COVID-19 experienced cognitive impairment after resolution of SARS-CoV-2 infection. We aimed to evaluate whether genetic liability to SARS-CoV-2 infection per se, or more severe COVID-19, is causally linked to cognitive deficit. Methods: We firstly performed univariable Mendelian randomization (MR) analysis to examine whether genetic liability to SARS-CoV-2 infection, hospitalized and severe COVID-19 is causally associated with cognitive performance. To dissect the causal pathway, multivariable MR (MVMR) analysis was conducted by adjusting for five inflammatory markers (C-reactive protein, interleukin [IL]-1β, IL-6, IL-8, and tumour necrosis factor α, as proxies of systemic inflammation). Results: In univariable MR analysis, host genetic liability to SARS-CoV-2 infection was associated with lower cognitive performance (inverse variance weighted [IVW] analysis, estimate: -0.023; 95% Confidence Interval [CI]: -0.038 to -0.009). Such causal association was attenuated in MVMR analysis when we adjusted for the five correlated inflammatory markers in one analysis (IVW analysis, estimate: -0.022; 95% CI: -0.049 to 0.004). There was insufficient evidence of association for genetic liability to hospitalized and severe COVID-19 with cognitive performance. Conclusion: The causal effect of host genetic liability to SARS-CoV-2 infection on reduced cognitive performance may be mediated by systemic inflammation. Future studies examining whether anti-inflammatory agents could alleviate cognitive impairment in SARS-CoV-2-infected individuals are warranted.